2002
DOI: 10.1038/sj.bjp.0704840
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the anandamide induced depolarization of guinea‐pig isolated vagus nerve

Abstract: 1 There is considerable interest in elucidating potential endogenously derived agonists of the vanilloid receptor and the role of anandamide in this regard has received considerable attention. In the present study, we have used an electrophysiological technique to investigate the mechanism of activation of vanilloid receptors in an isolated vagal preparation. 2 Both capsaicin and anandamide depolarized de-sheathed whole vagal nerve preparations that was antagonized by the VR1 antagonist, capsazepine (P50.05) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 54 publications
(90 reference statements)
4
23
0
Order By: Relevance
“…We found that afferents containing sensory neuropeptides were positive for TRPV1 in most regions of the trachea [15]. Others have shown that TRPV1 co-localizes with substance P within cell bodies of the jugular ganglion [6,7,8] and within airway epithelium in the respiratory tract [15, 16]. Chronic capsaicin administration causes the disappearance of TRPV1 immunoreactivity within the airways, again confirming the location of these receptors to sensory nerves [17].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…We found that afferents containing sensory neuropeptides were positive for TRPV1 in most regions of the trachea [15]. Others have shown that TRPV1 co-localizes with substance P within cell bodies of the jugular ganglion [6,7,8] and within airway epithelium in the respiratory tract [15, 16]. Chronic capsaicin administration causes the disappearance of TRPV1 immunoreactivity within the airways, again confirming the location of these receptors to sensory nerves [17].…”
Section: Introductionsupporting
confidence: 69%
“…The receptor belongs to the transient receptor potential family of proteins [3]. It is predominantly found on afferent nerve axons implicated in pain transduction [4, 5] and in afferents innervating the viscera [2], as well as in jugular and nodose ganglia that project into the lung [6,7,8]. Several stimuli associated with inflammation, such as low pH, heat and proinflammatory mediators including lipoxygenase mediators, activate TRPV1 [3, 9].…”
Section: Introductionmentioning
confidence: 99%
“…That PKC activation could lead to nociceptor hyperexcitability was further demonstrated by PMA, an activator of PKC, which produced hyperexcitability of a similar magnitude to antimycin A and H 2 O 2 . PMA and the activation of PKC have been shown previously to induce hyperexcitability in vagal nociceptive neurons (Kagaya et al, 2002;Ikeda et al, 2005;Lee, 2006, 2009;Matsumoto et al, 2007). PKC translocation from the cytosol to the plasma membrane is an indicator of PKC activation (CosentinoGomes et al, 2012).…”
mentioning
confidence: 98%
“…Activated PKC isoforms are capable of modifying neuronal excitability via the phosphorylation of numerous cellular targets, including ion channels and transporters. In particular, PKC has been shown to induce hyperexcitability via tetrodotoxin-resistant voltage-gated Na 1 channels in both vagal (Kagaya et al, 2002;Ikeda et al, 2005;Matsumoto et al, 2007) and DRG neurons (Baker, 2005;Hayase et al, 2007;Wu et al, 2012), indicating possible candidates for mitochondrial ROS-induced bronchopulmonary C-fiber hyperexcitability. However, given that tetrodotoxin-resistant voltage-gated Na 1 channels are expressed in both nociceptive and non-nociceptive neurons , further work is needed to elucidate the mechanism highlighted in the present study and its apparent exclusivity to nociceptive C-fibers.…”
mentioning
confidence: 99%
“…TRPV1 sensitization depends on several mechanisms among which phosphorylation of TRPV1 by protein kinase A (PKA), protein kinase C (PKC) and other kinases Fig. (1) is of pivotal importance [51,[58][59][60][61][62][63][64][65]. In fact, several inflammatory mediators (e.g.…”
Section: Trpv1 As Polymodal Sensor Expressed On Peptidergic Sensory Nmentioning
confidence: 99%